A further survey of the quantitative trait loci affecting swine body size and carcass traits in five related pig populations. (28th June 2021) - Li, L.‐y.; Xiao, S.‐j.; Tu, J.‐m.; Zhang, Z.‐k.; Zheng, H.; Huang, L.‐b.; Huang, Z.‐y.; Yan, M.; Liu, X.‐d.; Guo, Y.‐m.
Summary: Breeding for good meat quality performance while maintaining large body size and desirable carcass traits has been the major challenge for modern swine selective breeding. To address this goal, in the present work we studied five related populations produced by two commercial breeds (Berkshire and Duroc) and two Chinese breeds (Licha black pig and Lulai black pig). A single‐trait GWAS performed on 20 body size and carcass traits using a self‐developed China Chip‐1 porcine SNP50K BeadChip identified 11 genome‐wide significant QTL on nine chromosomes and 22 suggestive QTL on 15 chromosomes. For the 11 genome‐wide significant QTL, eight were detected in at least two populations, and the rest were population‐specific and only mapped in Shanxia black pig. Most of the genome‐wide significant QTL were pleiotropic; for example, the QTL around 75.65 Mb on SSC4 was associated with four traits at genome‐wide significance level. After screening the genes within 50 kb of the top SNP for each genome‐wide significant QTL, NR6A1 and VRTN were chosen as candidate genes for vertebrae number; PLAG1 and BMP2 were identified as candidate genes for body size; and MC4R was the strong candidate gene for body weight. The four genes have been reported as candidates for thoracic vertebrae number, lumbar vertebrae number, carcass length and body weight respectively in previous studies. The effects of VRTN on thoracic vertebrae number, carcass length and body length have been verified in Shanxia black pig. Therefore, the VRTN genotype could be used in gene‐assisted selection, and this could accelerate genetic improvement of body size and carcass traits in Shanxia black pig.